Microplastics in the surgical environment - Field, Daniel T.; Green, Jordan L.; Bennett, Robert; Jenner, Lauren C.; Sadofsky, Laura.R.; Chapman, Emma; Loubani, Mahmoud; Rotchell, Jeanette M. (Environment International, 2022)
Atmospheric microplastics (MPs) have been consistently detected within indoor and outdoor air samples. Locations with high human activity are reported to have high MP levels. The aim was to quantify and characterise the MPs present within the surgical environment over a one-week sampling period. MPs were collected in samplers placed around an operating theatre and adjoining anaesthetic room at 12 h intervals. Particles were filtered onto 0.02 µm membranes and analysed using micro-Fourier-transform infrared spectroscopy. The number of MPs identified during the working day sampling period varied, with a mean of 1,924 ± 3,105 MP m−2 day−1 and a range of 0 – 9,258 MP m−2 day−1 observed in the theatre, compared with a mean of 541 ± 969 MP m−2 day−1 and a range of 0 – 3,368 MP m−2 day−1 for the anaesthetic room. Across both rooms and at all sampling points, an increase in levels with a decrease in MP size was observed. Identified particles consisted of mainly fragment shaped MPs (78 %) with polyethylene terephthalate (37 %), polypropylene (25 %), polyethylene (7 %) and nylon (13 %) representing the most abundant polymer types. MPs were not detected in the theatre during non-working hours. The results provide novel information on defining polymer levels and types, in a room environment where the use of single plastics has been regarded as beneficial to practice. These results can inform cellular toxicity studies, investigating the consequences of human MP exposure as well as represent a potentially novel route of exposure for humans for this emerging contaminant of concern, via surgery.
Keywords: Microplastic; Polymer; Deposition; Synthetic; Surgery; Air; FTIR